Program Smart Surau dalam Membentuk Kebiasaan Salat Berjamaah Anak Melalui Sinergi Keluarga, Sekolah, dan Masjid di Kota Padang - Dipalpa Rego; Ikhwan Al Hafiz; Mutiara Heidi Fernanda; Muhammad Kosim (Universitas Serambi Mekkah, 2026)
This study aims to analyze the success of the Smart Surau Program in fostering children’s habit of performing congregational prayers through the synergy of family, school, and mosque at Hidayatunnur Baini Mosque in Padang City. The study employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving children, parents, teachers, and mosque administrators as research informants. Data analysis was conducted through data reduction, data display, and conclusion drawing to obtain an in-depth understanding of the process of developing congregational prayer habits among children. The findings reveal that the success of the Smart Surau Program is not solely determined by mosque-based activities but also by continuous collaboration among family, school, and mosque. Families provide early habituation and role modeling, schools reinforce religious values through religious culture and activities, while mosques offer opportunities for the practical implementation of religious practices. The synergy among these three educational environments successfully develops consistent congregational prayer habits among children, even without direct supervision. Over time, these habits evolve into intrinsic motivation, making congregational prayer a spiritual necessity rather than an imposed obligation. The study concludes that the integration of family, school, and mosque roles is the key factor in strengthening children’s religious character through the Smart Surau Program